1992
DOI: 10.1155/1992/34586
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Switch Macrophages Can Present Antigen

Abstract: Recent reports of “lineage switching” from a lymphoid to macrophage phenotype have left unresolved the question of whether such cells are functional macrophages or nonfunctional products of differentiation gone awry. This study demonstrates that several “macrophage-like” cell lines derived from v-Ha-ras-transformed pre-B cells have gained the capacity to effectively present antigen in MHC-restricted fashion. Using an assay involving the cocultivation of putative antigen-presenting cells with chicken ovalbumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a recent article, McClellan and colleagues reported that when incubated in vitro , blasts from some precursor B-cell acute lymphoblastic leukemia cells could apparently be functionally reprogrammed into myeloid lineage-mimicking cells that morphologically resemble and can, in some cases, function similarly to normal MPs ( 111 ). Several other studies had similar findings, demonstrating that malignant B-lymphoid cells can be reprogrammed to become MPs with apparently lymphoid and myeloid characteristics under certain conditions ( 112 115 ). Interestingly, we observed a similar phenomenon in MCL cases, as in vitro culture of primary MCL cells led to the presence of MPs after several days ( 70 ).…”
Section: Origin Of Tams In B-cell Lymphomasmentioning
confidence: 54%
“…In a recent article, McClellan and colleagues reported that when incubated in vitro , blasts from some precursor B-cell acute lymphoblastic leukemia cells could apparently be functionally reprogrammed into myeloid lineage-mimicking cells that morphologically resemble and can, in some cases, function similarly to normal MPs ( 111 ). Several other studies had similar findings, demonstrating that malignant B-lymphoid cells can be reprogrammed to become MPs with apparently lymphoid and myeloid characteristics under certain conditions ( 112 115 ). Interestingly, we observed a similar phenomenon in MCL cases, as in vitro culture of primary MCL cells led to the presence of MPs after several days ( 70 ).…”
Section: Origin Of Tams In B-cell Lymphomasmentioning
confidence: 54%
“…CD45 is a transmembrane PTP of hematopoietic cells composed of 1268 total amino acids with an external domain containing alternately used exons, which leads to the lymphocyte-specific expression of at least eight different isoforms (1,5,6). The cytoplasmic domain consists of 702 amino acids and contains two tandem repeated PTP domains designated D1 and D2 (1).…”
mentioning
confidence: 99%
“…Total cellular RNA was analyzed by RT-PCR as previously described (26). Basically, 0.5 to 1.0 pg of RNA was reverse transcribed into cDNA using a 3' antisense oligonucleotide primer specific for murine CD45 exon 9 described by Bretz et al (26).…”
Section: Molecular Analysesmentioning
confidence: 99%
“…Basically, 0.5 to 1.0 pg of RNA was reverse transcribed into cDNA using a 3' antisense oligonucleotide primer specific for murine CD45 exon 9 described by Bretz et al (26). One-half of the cDNA samples were amplified for 35 cycles in a 50 pl PCR reaction mixture containing 500 pM dNTPs and 400 ng of the 5' (specific to exon 2) and 3' oligonucleotides according to the conditions described previously (26). Reaction products were analyzed on 2% NuSieve gel stained with ethidium bromide.…”
Section: Molecular Analysesmentioning
confidence: 99%